The Effect of Leadership Style and Work Discipline on Employee Performance at the Central Jakarta Tourism Ministry - Iman Syatoto (PINISI Discretion Review, 2020)
Almost all fields of work and human activities depend on information technology. This study was to determine the effect of leadership style and work discipline on employee performance at the Ministry of Tourism in Central Jakarta. The method used in this research is descriptive with an associative approach, the sampling technique used is proportional random sampling using the census or saturated sampling method with a sample of 50 respondents. The analysis tool uses instrument testing, classical assumption testing, regression testing, determination coefficient testing and hypothesis testing. The results of the study concluded that there was a positive and significant influence both partially and simultaneously between leadership style and work discipline on employee performance at the Ministry of Tourism with a contribution of 0.486 or 48.6% while the remaining 51.4% was influenced by other factors. Hypothesis testing is obtained Fcount> Ftable (22,261> 2,800) thus H0 is rejected and H3 is accepted meaning that there is a positive and significant simultaneous influence between leadership style and work discipline on employee performance at the Ministry of Tourism in Central Jakarta.